(untitled) (Journal of Information Technologies in Education (ITE), 2010)
The article presents a brief description of the features of the IDE of the course "Basis of algorithmization and programming" developed by the laboratory of integrated environments of learning RI IT in Kherson State University. As part of the disclosure of the theme "The computational experiment" are examples of solutions and analyze the efficiency of sorting algorithms for arrays of different length, is visual representation of their work means the module "Demonstration Environment", and also demonstrated several ways to determine the complexity of the execution time.